Pelatihan Finansial Melalui Pengenalan Laporan Keuangan Pada UMKM kota Solok - ., Murnati; Raflis, Ratnawati; ., Rahmaita; ., Nini; ., Maivalinda; Hasnita RC, Rita Sri; Sulistianingsih, Henny; Turay, Tiara; Chairoel, Lucy; ., Firsta (LPPM Universitas Dharma Andalas, 2025)
Improving Financial Knowledge Financial reporting for MSMEs in Solok City is essential, considering that accounting is one of the competencies offered to these MSMEs. To provide in-depth knowledge about finance, a team of lecturers from Dharma Andalas University held a community service activity for MSMEs in Solok City. This activity was carried out by providing material related to knowledge about financial reports in accordance with currently applicable accounting standards. The number of people who participated in this Financial training activity was 61 people from Solok City. After this activity, the community, especially MSMEs in Solok City, learned the types and forms of company financial reports that comply with currently applicable standards.